Immunoregulatory CD4-CD8- T cells as a potential therapeutic tool for transplantation, autoimmunity, and cancer - Hillhouse, Erin E.; Delisle, Jean-Sébastien; Lesage, Sylvie (Frontiers in Immunology, 2013)
A central objective in organ transplantation and the treatment or prevention of autoimmune disease is the achievement of antigen-specific immune tolerance. An additional challenge in bone marrow transplantation for the treatment of hematological malignancies is the prevention of graft-vs-host disease (GVHD) while maintaining graft-vs-tumor activity. Interestingly, CD4-CD8- (double negative, DN) T cells, which exhibit a unique antigen-specific immunoregulatory potential, appear to exhibit all of the properties to respond to these challenges. Herein, we review the therapeutic potential of immunoregulatory DN T cells in various immunopathological settings, including graft tolerance, GVHD, cancer and autoimmunity.